The Refusal of Speech Acts - Kartini Br Bangun; Margaret Stevani (LOMBOK JOURNAL OF SCIENCE, 2020)
Speech act was an action that was manifested in the form of speech. Speech acts of refusal were an expression in the form of speech or utterance that contained information or response refuse submitted by a person or group. The purpose of this study was to describe the form of language refusal and the factors that influencing the language form of the refusal. The methods used in data collection were SLC (Listening/simak, involving/libat, and talking/cakap) method, SLBC (Listening/simak, free/bebas, involving/libat, and talking/cakap) method and field notes. The results of the research obtained from the form of the language of refusal were: 1. The use of non-verbal cues or refusal, 2. The use of comments as refusal, 3. The use of gratitude and accompanied by a reason of refusal, 4. Refusal by proposal or choice, 5. The use of terms, 6. Giving refusal reasons, and 7. Using word No or The equivalent. Meanwhile, the Factors that affecting the form of language refusal were: 1. Speaker condition (the person who speaks of refusal), 2. Familiarity between speakers with the interlocutor (the person who refused and the interlocutor response (offer, invite or request), and the situation at the time of the speech took place. Keywords: Speech Acts, Refusal, The Form of The Language Refusal